Effects of Dietary Fermented Flammulina velutipes Mycelium on Performance and Egg Quality in Laying Hens - Lee, Sang-Bum; Im, Jintaek; Kim, Seon-Ku; Kim, Youn-Chil; Kim, Min-Jeung; Lee, Jae-Seung; Lee , Hong-Gu (International Journal of Poultry Science, 2014)
This study was conducted to evaluate the effect of dietary Flammulina velutipes mycelium (FFVM) fermented with Bacillus subtilis A8-8 and Klebsiella sp. Sc on the performance of laying hens including the egg quality, the pathogenic bacterial (Escherichia coli and Salmonella spp.) counts in caecal contents and the NH3 production in excreta. One hundred eighty Hy-Line Brown hens were fed one of six diets, including a corn-soybean meal based control diet and control diets supplemented with FFVM at 1, 2, 3, 4, or 5% (n = 30 per experimental group). During the 5 week experimental period, laying hen performance, egg quality, pathogenic bacteria number in caecum and fecal NH3 gas production were estimated. Although there were no significant differences in egg production, feed intake and feed conversion among experimental groups, egg weight was significantly increased in the 1 and 3% FFVM groups compared with the control diet group (p<0.05). Interestingly, the 4% FFVM experimental group improved egg quality including albumen height, Haugh unit, egg shell weight and shell thickness, but not yolk color (p<0.05). On the other hand, the number of pathogenic bacteria such as Salmonella spp. and E. coli in caecum was significantly decreased by high levels of dietary FFVM supplementation (3-5%) (p<0.05). Early stage fecal NH3 gas production was also significantly suppressed by 3-5% dietary FFVM diets (p<0.05). Collectively, our results indicated that high level of dietary FFVM (4%) improves egg quality as well as suppressing pathogenic bacterial proliferation in the gastrointestinal tract and fecal NH3 gas emission.